Rhizosphere of tress that accumulate phosphorus in the Brazilian Amazon. - Chavez de Oliveira, Patricia; Universidade Federal do Oeste do Pará - UFOPA, Laboratório de Estudos de Ecossistemas Amazônicos- LEEA , Santarém, Pará, Brasil. (Pontificia Universidad Javeriana, 2011)
Objective. With the purpose of knowing the strategies of tolerance of two phosphorus-accumulating species (Neea macrophylla and Cecropia palmate) and a non-accumulating species (Casearia arborea) to phosphorus-deficient soils, we characterized the rhizosphere of these species using a multivariate analysis and correlation matrices in relation to the concentrations of organic phosphorus, available phosphorus, soil organic carbon, organic carbon from  microbial biomass,  acid phosphatase enzyme activity, and root infection by mycorrhizal fungi. Materials and methods. The research was carried out in the Igarapé-Açú town, state of Pará, Brazil in secondary forests with five years of regeneration, where the parameters above mentioned were monitored. Results. Results did not reveal significant differences between the species depending on the characteristics of the soil next to the rhizospheres, suggesting homogeneous conditions. The enzymatic activity was slightly higher in the species with less potential in accumulating P (Casearia arborea) suggesting that efficiency in P use is not determined by the enzymatic activity. Conclusions. Neea macrophylla presented a slightly higher number of mycorrhizal root infections in comparison to the other species, indicating that this could be a tolerance strategy in those environments, while in Cecropia palmata and Casearia arborea it seems that enzymatic activity is the strategy employed. Key words: acid phosphatase; Brazilian Amazon; rhizosphere